(untitled) (International Journal of Engineering and Computer Science, 2018)
Mobile Ad hoc networks (MANET) are a new paradigm of networks offering unrestricted mobility without any underlying infrastructure. The network is set up with a group of mobile wireless nodes and is devoid of any dedicated routers or base stations. The wireless nodes move around freely and mutually cooperate with each other in routing and forwarding packets without the support of any fixed infrastructure or centralized administration. The topology is highly dynamic, making the routing procedure more difficult and insecure. In this paper, the performance of the network is analyzed after flooding the network using malicious nodes. The flooding attack is done by the malicious node by sending fake RREQ packets throughout the network. The number of malicious nodes and their position is changed along with various other node characteristics to observe their respective effects on the network performance. The simulation environment is implemented by using the NS-3 network simulator.